1978
DOI: 10.1366/000370278774331710
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Total Iron in Venezuelan Laterites: The Investigation of Interferences of Aluminum and Silicon on the Determination of Iron in the Fluoboric-Boric Acid Matrix by Atomic Absorption

Abstract: An interference-free atomic absorption method for the determination of total iron in geological samples has been adopted. The method is based on the conventional standard curve technique employing the 386 nm atomic absorption line in the fluoboric-boric acid matrix. The use of the 386 nm line instead of the 248.3 nm line is discussed, as well as the advantages of the hydrofluoric acid dissolution of the sample. A comparison of different methods is given in search of one for routine determinations in this labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The suspension was centrifuged, and Fe, AI, and Si were determined in the decanted clear supernatant by atomic absorption spectroscopy (AA) using a N20-C2H2 flame. The solids were analyzed for total iron in a fluoboric-boric acid matrix (La Brecque et al, 1978). In order to remove completely the free iron oxides, 8 consecutive extractions with CDB were necessary for sample a and 15 for samples b and c. The amount of Fe203 dissolved after further extractions with CDB was <0.01%.…”
Section: Selective Chemical Dissolution With Dithionitementioning
confidence: 99%
“…The suspension was centrifuged, and Fe, AI, and Si were determined in the decanted clear supernatant by atomic absorption spectroscopy (AA) using a N20-C2H2 flame. The solids were analyzed for total iron in a fluoboric-boric acid matrix (La Brecque et al, 1978). In order to remove completely the free iron oxides, 8 consecutive extractions with CDB were necessary for sample a and 15 for samples b and c. The amount of Fe203 dissolved after further extractions with CDB was <0.01%.…”
Section: Selective Chemical Dissolution With Dithionitementioning
confidence: 99%
“…Iron has been determined in iron ores (101,231,291,303,416) and manganese nodules (143,313) by activation with neutrons and y-ray spectrometry. Atomic absorption methods have been developed for the determination of iron in slags (72,226), ores (173,281), and steel (310). Spectrophotometric methods were used for this determination in ferroalloys (379), steel (372), and ores (130,389,515).…”
Section: Inclusionsmentioning
confidence: 99%
“…A reduction in matrix effect errors is claimed and the method was applied to the analysis of aluminum alloys. Yoshimura and Morimoto (281) reported that the interference of fluoride and phosphate on the atomic absorption determination of Al and Ti could be reduced with carbon black powder.…”
Section: Procedures For Multiple Constituentsmentioning
confidence: 99%